Therapeutic Approaches of Nanotechnology for Epileptic Seizures: A Comprehensive Review of Current Knowledge - Shrivastava, Aman; Gupta, Jeetendra K; Goyal, Manoj K (Indian Journal of Pharmaceutical Education and Research, 2022)
Epilepsy is a chronic neurological condition in which several neurotransmitters act like neuromodulators. The symptoms of epilepsy are caused by abnormal electrical discharges in a group of neurons in the hippocampus region of the brain. This can also affect electrical impulse generation, either in the focal area or in the hippocampus region of the brain. This review aimed to develop a better understanding of the transportation of nanoparticles across the blood-brain barrier and how to enhance the delivery of the drug in epileptic conditions by the utilization of nanomaterials. A few clinical studies have reported that antiepileptic drugs are generally used for the treatment of epilepsy by decreasing the frequency and intensity of seizures or preventing tissue damage in the brain. In longterm therapy, antiepileptic drugs are primarily administered via the oral route, but they are not always beneficial. Therefore, intravenous routes are especially used in serious epileptic conditions. In this review, we discussed the drug delivery study of antiepileptic drugs that are used in the form of nanoparticles that can easily be transported across the blood-brain barrier. Besides, the nanoparticles can easily cross the blood-brain barrier and increase the uptake into the target cells. Drug absorption into the brain is substantially limited by some factors, especially in the blood-brain barrier, which affects the potency of antiepileptic drugs to reach and remain inside the brain. Novel drug delivery systems have already been studied in many clinical trials to enhance the therapeutic efficacy of antiepileptic drugs in epileptic conditions.
Keywords: Epilepsy; Nanotechnology; Drug delivery; Movement of nanoparticle; Neurodegenerative disorder